Spontaneous Ureteral Stent Fragmentation: A Case Report and Review of the Literature - Mete Kilciler; Fikret Erdemir; Selahattin Bedir; Hidayet Coban; Koray Erten; Oguz Guven; Hasret Topac (Kaohsiung Journal of Medical Sciences, 2006)
Ureteral stents have been widely used for more than two decades with different indications. Due to the widespread usage of ureteral stents, the number of possible complications of ureteral stents has increased, including stent migration, encrustation, stone formation, and fragmentation. Among these complications, ureteral stent fragmentation is rare. Herein, we present a case of spontaneous ureteral stent fragmentation and review the relevant literature.